More efficient adaptation of cardiovascular response to repeated restraint in spontaneously hypertensive rats: the role of autonomic nervous system - Vavřínová, Anna; Behuliak, Michal; Vodička, Martin; Bencze, Michal; Ergang, Peter; Vaněčková, Ivana; Zicha, Josef (Hypertension research, 2024)
We hypothesized that sympathetic hyperactivity and parasympathetic insuficiency in spontaneously hypertensive rats (SHR) underlie their exaggerated cardiovascular response to acute stress and impaired adaptation to repeated restraint stress exposure compared to Wistar-Kyoto rats (WKY). Cardiovascular responses to single (120 min) or repeated (daily 120 min for 1 week) restraint were measured by radiotelemetry and autonomic balance was evaluated by power spectral analysis of systolic blood pressure variability (SBPV) and heart rate variability (HRV). Baroreflex sensitivity (BRS) was measured by the pharmacological Oxford technique. Stress-induced pressor response and vascular sympathetic activity (low-frequency component of SBPV) were enhanced in SHR subjected to single restraint compared to WKY, whereas stress-induced tachycardia was similar in both strains. SHR exhibited attenuated cardiac parasympathetic activity (high-frequency component of HRV) and blunted BRS compared to WKY. Repeated restraint did not affect the stress-induced increase in blood pressure. However, cardiovascular response during the post-stress recovery period of the 7th restraint was reduced in both strains. The repeatedly restrained SHR showed lower basal heart rate during the dark (active) phase and slightly decreased basal blood pressure during the light phase compared to stress-naive SHR. SHR subjected to repeated restraint also exhibited attenuated stress-induced tachycardia, augmented cardiac parasympathetic activity, attenuated vascular sympathetic activity and improved BRS during the last seventh restraint compared to single-stressed SHR. Thus, SHR exhibited enhanced cardiovascular and sympathetic responsiveness to novel stressor exposure (single restraint) compared to WKY. Unexpectedly, the adaptation of cardiovascular and autonomic responses to repeated restraint was more effective in SHR.
Keywords: potkani inbrední WKY; Male; hypertenze; Restraint, Physical; Habituation; Autonomic Nervous System; Adaptation, Physiological; psychický stres; Heart Rate; Restraint stress; potkani inbrední SHR; Adaptation; Baroreflex; mužské pohlaví; srdeční frekvence; fyziologická adaptace; fyzické omezení; Hypertension; krysa rodu Rattus; autonomní nervový systém; Animals; krevní tlak; zvířata; Stress, Psychological; Rats; Blood Pressure; Rats, Inbred SHR; Rats, Inbred WKY; baroreflex; Adrenal glands